Intratumoral immunotherapy with TLR7/8 agonist MEDI9197 modulates the tumor microenvironment leading to enhanced activity when combined with other immunotherapies. Issue 1 (11th September 2019) - Mullins, Stefanie R.; Vasilakos, John P.; Deschler, Katharina; Grigsby, Iwen; Gillis, Pete; John, Julius; Elder, Matthew J.; Swales, John; Timosenko, Elina; Cooper, Zachary; Dovedi, Simon J.; Leishman, Andrew J.; et al.
Abstract : Background: Immune checkpoint blockade (ICB) promotes adaptive immunity and tumor regression in some cancer patients. However, in patients with immunologically "cold" tumors, tumor-resident innate immune cell activation may be required to prime an adaptive immune response and so exploit the full potential of ICB. Whilst Toll-like receptor (TLR) agonists have been used topically to successfully treat some superficial skin tumors, systemic TLR agonists have not been well-tolerated. Methods: The response of human immune cells to TLR7 and 8 agonism was measured in primary human immune cell assays. MEDI9197 (3M-052) was designed as a novel lipophilic TLR7/8 agonist that is retained at the injection site, limiting systemic exposure. Retention of the TLR7/8 agonist at the site of injection was demonstrated using quantitative whole-body autoradiography, HPLC-UV, and MALDI mass spectrometry imaging. Pharmacodynamic changes on T cells from TLR7/8 agonist treated B16-OVA tumors was assessed by histology, quantitative real time PCR, and flow cytometry. Combination activity of TLR7/8 agonism with immunotherapies was assessed in vitro by human DC-T cell MLR assay, and in vivo using multiple syngeneic mouse tumor models. Results: Targeting both TLR7 and 8 triggers an innate and adaptive immune response in primary human immune cells, exemplified by secretion of IFNα, IL-12 and IFNγ. In contrast, a STING or a TLR9 agonist primarily induces release of IFNα. We demonstrate that the TLR7/8 agonist, MEDI9197, is retained at the sight of injection with limited systemic exposure. This localized TLR7/8 agonism leads to Th1 polarization, enrichment and activation of natural killer (NK) and CD8 + T cells, and inhibition of tumor growth in multiple syngeneic models. The anti-tumor activity of this TLR7/8 agonist is enhanced when combined with T cell-targeted immunotherapies in pre-clinical models. Conclusion: Localized TLR7/8 agonism can enhance recruitment and activation of immune cells in tumors and polarize anti-tumor immunity towards a Th1 response. Moreover, we demonstrate that the anti-tumor effects of this TLR7/8 agonist can be enhanced through combination with checkpoint inhibitors and co-stimulatory agonists.